The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1136/bmj.329.7458.152
|View full text |Cite
|
Sign up to set email alerts
|

Threatened miscarriage: evaluation and management

Abstract: Threatened miscarriage-vaginal bleeding before 20 gestational weeks-is the commonest complication in pregnancy, occurring in about a fifth of cases.w1 Miscarriage is 2.6 times as likely, 1 and 17% of cases are expected to present complications later in pregnancy. 2Although general practitioners and gynaecologists often see this condition, management of threatened miscarriage is mostly empirical. Bed rest is routinely recommended, and about a third of women presenting with threatened miscarriage are prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 22 publications
1
58
0
5
Order By: Relevance
“…It occurs in about a fifth of all pregnancies and approximately half of them will be lost. Progesterone is an essential hormone for the continuation of pregnancy and is prescribed in 13-40% of women with threatened miscarriage, according to the literature [8]. Some authors suggested that progesterone reduced the abortion rate in women with threatened miscarriage [7].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in about a fifth of all pregnancies and approximately half of them will be lost. Progesterone is an essential hormone for the continuation of pregnancy and is prescribed in 13-40% of women with threatened miscarriage, according to the literature [8]. Some authors suggested that progesterone reduced the abortion rate in women with threatened miscarriage [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several review articles and book chapters also exist at present concerned primarily with the evaluation, management, and treatment of threatened abortion (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The American College of Emergency Physicians has begun to develop a clinical policy statement and evaluation algorithms to aid in the evaluation of threatened abortion (1,9 -11).…”
Section: Discussionmentioning
confidence: 99%
“…These will enable Emergency Physicians to treat these patients with improved diagnostic accuracy after observations in the past of falling well "short of reasonable standards" (23). These evaluation parameters insist that a history and physical examination, sonographic evaluation, and laboratory testing of maternal serum biochemistry be the mainstay of evaluation in these patients (8). On pelvic examination, if the os is open or products of conception are seen, the diagnosis of inevitable miscarriage is made, and after counseling the patient, OB/GYN consultation is scheduled while inhouse or as an outpatient after discharge (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Threatened miscarriage, defined as vaginal bleeding before the 20th week of gestation, occurs in about 20% of pregnancies [1]. One in three women with threatened miscarriage subsequently suffers a complete miscarriage [2].…”
Section: Introductionmentioning
confidence: 99%